New Insights Into the Peculiar World of the Shepherd-Dog Parasites: An Overview From Maremma (Tuscany, Italy) - Morandi, Benedetto; Mazzone, Angelica; Gori, Francesca; Alvarez Rojas, Cristian A.; Galuppi, Roberta; Deplazes, Peter; Poglayen, Giovanni (Frontiers in Veterinary Science, 2020)
Several developments have been recently achieved to understand pet-dog parasites and their relationship with hosts; however, parasites' presence and distribution in shepherd-dog have been mainly neglected; this knowledge gap is of critical sanitary importance, as shepherd-dogs could harbor zoonotic helminths including Echinococcus granulosus sensu lato. The related human disease, cystic echinococcosis, is a worldwide neglected disease, with high endemicity in the Mediterranean Basin. To evaluate the presence of E. granulosus and other parasites, a sheep-dog population from the province of Grosseto (Tuscany, Italy) has been investigated. Overall, 648 dog fecal samples obtained from 50 modern sheep farms, having a total of 216 dogs, were collected. Specimens were analyzed using a standardized centrifugal flotation method (specific gravity = 1.3). Taeniid eggs detected were further isolated using a sieving/flotation technique. DNA was isolated from eggs for PCR and sequence analyses for species identification (gene target: 12S rRNA and nad1). Thirty-nine (78%) farms tested positive for at least one parasite species or genus. The most represented intestinal helminths were Toxocara spp. in 64% of farms, followed by Ancylostomatidae (58%), Trichuris vulpis (50%), Capillaria spp. (34%), and taeniids (32%). Sequence analyses confirmed the presence of Taenia hydatigena in seven farms, Taenia (syn. Multiceps) multiceps in five farms, and T. pisiformis in one farm. No DNA was extracted from four previously taeniid egg-positive farms. No amplification of amplicon corresponding to E. granulosus was achieved in the investigated farms. Although not entirely expected, Spearman's test showed a positive correlation between flock size and the number of dogs per farm (ρ = 0.588, P < 0.001). The quantitative analysis reported that the home slaughter practice was affected neither by the flock size nor by the number of dogs per farm. The probability to diagnose farms positive for taeniids had been increased by about 35% for each dog unit increase [odds ratio (OR) = 1.35, P = 0.012]. In conclusion, the wide distribution of T. hydatigena and T. multiceps detected in the present study clearly reveals that dogs have still access to raw offal, a major risk for the transmission of E. granulosus. Home slaughtering is an unavoidable practice, and more efforts must be undertaken by the public health system to prevent and control potential zoonotic taeniids.